2001
DOI: 10.1161/01.atv.21.1.61
|View full text |Cite
|
Sign up to set email alerts
|

ACE Inhibitor and AT 1 Antagonist Blockade of Deformation-Induced Gene Expression in the Rabbit Jugular Vein Through B 2 Receptor Activation

Abstract: Abstract-Deformation-induced endothelin-1 synthesis in endothelial cells may contribute to the intimal hyperplasia of venous bypass grafts. ACE inhibitors and angiotensin II type 1 (AT 1 ) receptor antagonists are capable of reducing vein graft disease. Therefore, the effects of these drugs on endothelial preproendothelin-1 (ppET-1) and smooth muscle endothelin B receptor (ET B -R) expression were investigated in isolated perfused segments of the rabbit jugular vein. Pretreatment with ramiprilat (0.3 mol/L) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
6
0
4
Order By: Relevance
“…These latter effects could be related to decreased pulmonary artery pressures, resulting in decreased shear stress-induced overexpression of ET-1. Losartan could also have inhibited an ANG II-induced inflammatory reaction, part of it being an overexpression of ET-1 (30), or could have prevented ANG II-induced ET-1 gene expression (9,12). It is of interest that losartan therapy reverted BMPR-2 expression to normal, which could also be related to decreased pulmonary artery pressures or to yet unknown interactions between BMPR-2 expression and ET-1 or ANG II signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…These latter effects could be related to decreased pulmonary artery pressures, resulting in decreased shear stress-induced overexpression of ET-1. Losartan could also have inhibited an ANG II-induced inflammatory reaction, part of it being an overexpression of ET-1 (30), or could have prevented ANG II-induced ET-1 gene expression (9,12). It is of interest that losartan therapy reverted BMPR-2 expression to normal, which could also be related to decreased pulmonary artery pressures or to yet unknown interactions between BMPR-2 expression and ET-1 or ANG II signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II (Ang II) receptors have a pathophysiological role in hypertension, cardiac hypertrophy and heart failure [49]. Ang II type 1 receptor (AT1R) is responsible for the majority of the effects of Ang II on the heart, including stimulated increases in heart rate, contractility, and cardiomyocyte growth [50].…”
Section: Role Of Rsps In Cardiovascular Pathologiesmentioning
confidence: 99%
“…Several studies have suggested that the RAAS is locally active in the healing vein graft wall and has an important role in vein graft remodeling (4,19,24,35). In addition, the inhibition of components of the RAAS has been shown to limit the progression of vein graft disease in experimental animal models (10,14,36).…”
Section: H44mentioning
confidence: 99%